1999
DOI: 10.1016/s0022-5347(05)68934-3
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNOCYT 1 : A NEW TOOL FOR DETECTING TRANSITIONAL CELL CANCER OF THE URINARY TRACT

Abstract: Immunocyt is a noninvasive, highly sensitive test for detecting transitional cell carcinoma of all grades and stages. When combined with conventional urinary cytology, it may replace cystoscopy in select patients, especially in followup protocols of low grade transitional cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
87
1
15

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(105 citation statements)
references
References 8 publications
2
87
1
15
Order By: Relevance
“…The combination of ImmunoCyt/uCytt with cytology may also help to detect nonvisible HG cancers, which are often missed by the cystoscopist. In our study, as in others, 7,14,20 all carcinomas in situ were found by combining cytology and ImmunoCyt/uCytt, while 50% had either negative or suspicious cytology. Reactive urothelial cells show mild abnormalities that are shared by LG neoplastic cells and require considerable screening time from pathologists and cytologists.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The combination of ImmunoCyt/uCytt with cytology may also help to detect nonvisible HG cancers, which are often missed by the cystoscopist. In our study, as in others, 7,14,20 all carcinomas in situ were found by combining cytology and ImmunoCyt/uCytt, while 50% had either negative or suspicious cytology. Reactive urothelial cells show mild abnormalities that are shared by LG neoplastic cells and require considerable screening time from pathologists and cytologists.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, in most studies, the sensitivity of ImmunoCyt/uCytt combined with cytology exceeds 80% when a threshold of 1 red or 1 green fluorescent cell is used. 6,7,[11][12][13][14] Our sensitivity of 84% means that, if a tumor is present, it would most likely be detected by the test. Therefore, if the test is positive, a cystoscopy should be performed and, if no tumor is seen, a tumor from the upper urinary tract should be suspected and ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Recently, 2 new methods for urine-bound detection of bladder cancer, that is, urinary hyaluronic acid and hyaluronidase levels, and the immunocytochemical test, Immunocyt, were introduced achieving high sensitivity and specificity levels of more than 80%. 24,25 In conclusion, MSA offers high sensitivity levels of up to 84.5% for the detection of bladder cancer-specific serum DNA alterations and 72% for the detection of urine sediment alterations. Of a panel of 17 microsatellite markers we could identify 5 from the chromosomal regions 8p, 9p and 9q that offered the highest sensitivity in diagnosing TCC-specific alterations in serum and urine of cancer patients.…”
Section: Discussionmentioning
confidence: 89%